PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA NASABAH PENGGUNA MOBILE BANKING - Untung Sriwidodo, Raditya Wisnu Wardana & (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the significance of the effect of service quality of mobile banking and satisfaction on loyalty and analyze the effect of the service quality of mobile banking on customer loyalty mediated by satisfaction. This study is a survey at consumers of Bank BNI Sukoharjo. Population are customer whose used mobile banking. Sample as many as 100 people with convenience sampling. The type of data used quantitative and qualitative data. Sources of data used primary data and secondary data. The technique of collecting data used questionnaires, observations and literature. Data were analyzed used path analysis. The survey results revealed that the service quality of mobile banking has a significant effect on customer satisfaction. Service quality of mobile banking has a significant effect on customer loyalty. Satisfaction has a significant effect on customer loyalty. Satisfaction mediate the effect of service quality of mobile banking on customer loyalty Keywords: service quality, satisfaction, loyalty, mobile banking